2020
DOI: 10.6004/jnccn.2020.0031
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Cancers, Version 2.2020, NCCN Clinical Practice Guidelines in Oncology

Abstract: Treatment is complex for patients with head and neck (H&N) cancers with specific site of disease, stage, and pathologic findings guiding treatment decision-making. Treatment planning for H&N cancers involves a multidisciplinary team of experts. This article describes supportive care recommendations in the NCCN Guidelines for Head and Neck Cancers, as well as the rationale supporting a new section on imaging recommendations for patients with H&N cancers. This article also describes updates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
630
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 837 publications
(704 citation statements)
references
References 230 publications
6
630
2
2
Order By: Relevance
“…The incidence of nasopharyngeal carcinoma (NPC) is high in south China and Southeast Asia [1]. Radiotherapy is the standard treatment modality, and a combination of radiotherapy and chemotherapy employed as the mainstay strategy [2]. Currently, induction chemotherapy (IC) combined with concurrent chemoradiotherapy is one of the most popular treatments for locoregionally advanced NPC, with confirmed therapeutic value.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of nasopharyngeal carcinoma (NPC) is high in south China and Southeast Asia [1]. Radiotherapy is the standard treatment modality, and a combination of radiotherapy and chemotherapy employed as the mainstay strategy [2]. Currently, induction chemotherapy (IC) combined with concurrent chemoradiotherapy is one of the most popular treatments for locoregionally advanced NPC, with confirmed therapeutic value.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the latest NCCN guidelines which suggest adjuvant radiotherapy for patients with pN1 disease, our results demonstrated that postoperative radiotherapy was effective only in those without good-quality neck dissection (LN yield < 18). 14,15 The protective effect of adjuvant radiotherapy failed to reach statistical signi cance for those with LN yield > 18. Because of the protective role of postoperative radiotherapy in oral and oropharyngeal cancer patients with pT1-2N1M0 disease without good-quality neck dissection, the NCCN guidelines for adjuvant radiotherapy in pN1 disease without adverse features may need to be modi ed according to the quality of retrieved LNs.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that patients with cancers of the hypopharynx and oropharynx had the highest excess risk of an SPC (Morris, Sikora, Patel, Hayes, & Ganly, ; Tiwana et al, ). Patients who are newly diagnosed with oral cancer usually receive head and neck imaging, such as computed tomography, magnetic resonance imaging, bone scans, and/or positron emission tomography, as part of the staging workup (Pfister et al, ). During surveillance, SPC in the oral cavity can usually be detected by oral inspection at an early stage, without compromising patient survival (Liao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…During surveillance, SPC in the oral cavity can usually be detected by oral inspection at an early stage, without compromising patient survival (Liao et al, ). However, SPC in the hypopharynx or esophagus cannot be detected by routine surveillance, because of anatomical alterations or sequelae, such as trismus, after the curative treatment (Pfister et al, ). Consequently, SPC‐HE is usually not detected in an early stage.…”
Section: Discussionmentioning
confidence: 99%